2015
DOI: 10.1007/s12551-014-0153-3
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for hypertrophic cardiomyopathy

Abstract: Hypertrophic cardiomyopathy (HCM) is a genetically determined cardiac disease characterised by otherwise unexplained myocardial hypertrophy of the left ventricle, and may result in left ventricular outflow tract obstruction. It is the most common cause of sudden cardiac death in young adults due to arrhythmias. Septal myectomy is a surgical treatment for HCM with moderate to severe outflow tract obstruction, and is indicated for patients with severe symptoms refractory to medical therapy. The surgical approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…3 Various accesses to reach and resect the hypertrophied myocardium to dilate the LVOT are described in the literature. 4,5 Transmitral access seems to be very suitable for septal myectomy particularly when mitral surgery is necessary. However, minimally invasive transmitral septal myectomy combined with MV surgery through right anterior mini-thoracotomy (RAMT) is rarely presented in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…3 Various accesses to reach and resect the hypertrophied myocardium to dilate the LVOT are described in the literature. 4,5 Transmitral access seems to be very suitable for septal myectomy particularly when mitral surgery is necessary. However, minimally invasive transmitral septal myectomy combined with MV surgery through right anterior mini-thoracotomy (RAMT) is rarely presented in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies of isolated septal myectomy report mortality rates up to 3%. 20 Four of the included studies reported early mortality rates below this. The two included studies with the highest mortality rates (6% 10 and 7% 17 ) reported mortality primarily due to respiratory failure and infection.…”
Section: Discussionmentioning
confidence: 98%
“…12 Various pharmacologic agents may be used to reduce the LVOT gradient and risk of sudden death, such as β-blockers, verapamil, diltiazem and disopyramide (Figure 1). 10,13 Procedural therapies to alleviate LVOTO in drug refractory HOCM include either sequential dual chamber pacing with short atrioventricular delay or surgical reduction therapies such as septal myectomy or septal alcohol ablation. 14,15 Surgical myectomy has been performed since the 1950s with efficacy rates exceeding 90%.…”
Section: Factors Influencing Hocmmentioning
confidence: 99%